The Effectiveness of Repetition in Increasing Students Vocabulary - Helmi Gunawan (SIMETRIS, 2020)
There are 2 problems that motivated the researchers to conduct this research. The first problems arises from internal and the second comes from external problems related to the weakness of engineering students in mastering English vocabulary. This study is intended to provide reinforcement to students on English vocabulary so that their English language skills increase. Through the repetition method, students are more likely to repeat and practice correct spelling when pronouncing English words. In addition, the ability to concoct sentences can also be trained with this method. The data in the form of field notes and questionnaire results show that with repetition students are able to increase English vocabulary accompanied by an increase in creating sentences.